2012
DOI: 10.1053/j.gastro.2012.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Cannabinoid Receptor-1 Mediates Diet-Induced Insulin Resistance via Inhibition of Insulin Signaling and Clearance in Mice

Abstract: BACKGROUND & AIMS Obesity-related insulin resistance contributes to cardiovascular disease. Cannabinoid receptor-1 (CB1) blockade improves insulin sensitivity in obese animals and people, suggesting endocannabinoid involvement. We explored the role of hepatic CB1 in insulin resistance and inhibition of insulin signaling pathways. METHODS Wild-type mice and mice with disruption of CB1 (CB1−/− mice) or with hepatocyte-specific deletion or transgenic overexpression of CB1 were maintained on regular chow or a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
174
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 158 publications
(197 citation statements)
references
References 57 publications
19
174
2
2
Order By: Relevance
“…Moreover, CB1R inhibition did not significantly alter phosphorylation of IRS‐1 at Ser307 (Fig. 5B), a site whose phosphorylation in response to CB1R activation has been associated with suppressed IRS‐1/PKB dependent signalling (Liu et al ., 2012). Indeed, this is consistent with our previous work demonstrating the ability of rimonabant to enhance insulin sensitivity in rat L6 myotubes, an in vitro skeletal muscle model, without altering upstream IRS‐1/PI3K signalling (Lipina et al ., 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, CB1R inhibition did not significantly alter phosphorylation of IRS‐1 at Ser307 (Fig. 5B), a site whose phosphorylation in response to CB1R activation has been associated with suppressed IRS‐1/PKB dependent signalling (Liu et al ., 2012). Indeed, this is consistent with our previous work demonstrating the ability of rimonabant to enhance insulin sensitivity in rat L6 myotubes, an in vitro skeletal muscle model, without altering upstream IRS‐1/PI3K signalling (Lipina et al ., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, this is consistent with our previous work demonstrating the ability of rimonabant to enhance insulin sensitivity in rat L6 myotubes, an in vitro skeletal muscle model, without altering upstream IRS‐1/PI3K signalling (Lipina et al ., 2010). Therefore, we next focussed on alternative pathways involving the potential modulation of PHLPP1 and PP2A (protein phosphatase 2A), two key negative regulators which act to dephosphorylate and inactivate PKB/Akt (Resjo et al ., 2002; Liu et al ., 2012). Rimonabant treatment did not alter levels of PHLPP1 protein in aged gastrocnemius muscle (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Datos de la literatura indican que hay una correlación positiva entre las concentraciones de 2-AG en sangre arterial y venosa hepática y el contenido de lípidos en hígado 33 . Adicionalmente, un estudio reciente demostró un robusto aumento de RCB 1 hepáticos en individuos con hígado graso no alcohólico 34 . El impacto del SEC sobre la esteatosis hepática se ha investigado más acuciosamente en pacientes con hepatitis C, en los cuales la prevalencia de esteatosis es de 30-70%, ya sea como consecuencia de perturbaciones metabólicas asociadas o bien por los efectos esteatogénicos propios del genotipo 3 del virus de la hepatitis C. En un estudio prospectivo en pacientes con hepatitis C no tratados, el uso diario de Cannabis durante 6 meses se reconoció como un predictor independiente de esteatosis severa 35 .…”
Section: Evidencia Clínicaunclassified
“…Finalmente, es importante considerar que el SEC hepático no sólo participa en la fisiología y fisiopatología del hígado, sino que también está implicado en otros efectos sistémicos asociados al síndrome metabólico, como es el caso de la dislipidemia y resistencia a insulina y leptina 20,34 .…”
Section: Conclusionesunclassified
“…However, even if the CB1R-dependent stimulation of food intake may be the main initial cause of various metabolic deregulations associated with obesity, several data collected from animal and human studies using the specific CB1R antagonist SR141716 (rimonabant) suggested that peripheral ECS might also directly regulate energy metabolism (6)(7)(8). It was recently reported that activation of peripheral CB1R signaling in key tissues relevant to insulin action is associated with alteration of glucose homeostasis and contributes to diet-induced insulin resistance in mice (9)(10)(11). Nevertheless, very little information is available concerning the impact of peripheral ECS activation on intestinal glucose absorption that is however the major determinant of how quickly glucose appears in the circulation during the fed state.…”
mentioning
confidence: 99%